The All-Oneness Principle in V. Solovyov’s Ontology - Šliogeris, Arvydas (Problemos, 1975)
The article presents an analysis of some aspects of the ontological interpretation of the all-oneness principle as suggested by V. Solovyov, a Russian philosopher-idealist of the late 19th century. All-oneness appears as the main structural element of the absolute origin of being – the all one being. By applying this principle V. Solovyov substitutes the traditional dualistic structure of being which as a kind of pantheistic schema is adopted in the “classical” Christianity, i.e., by introducing pantheistic elements he relaxes the dualistic tension. The social, social-psychological and theoretical prerequisites for the necessity of the dualistic ontology are analysed in the paper. The original assumptions and final results of V. Solovyov’s religious-idealistic ontology are criticized from the Marxist point of view, the anti-scientific essence of the ontological interpretation of the all-oneness principle is disclosed.